2022
DOI: 10.1021/acsmaterialsau.2c00020
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Modifications Suppress Anharmonic Effects in the Lattice Dynamics of Organic Semiconductors

Abstract: The lattice dynamics of organic semiconductors has a significant role in determining their electronic and mechanical properties. A common technique to control these macroscopic properties is to chemically modify the molecular structure. These modifications are known to change the molecular packing, but their effect on the lattice dynamics is relatively unexplored. Therefore, we investigate how chemical modifications to a core [1]benzothieno-[3,2-b]benzothiophene (BTBT) semiconducting crystal affect the evoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…However, some of us recently showed that the polarization–orientation (PO) Raman response, i.e., the polarization dependence of the Raman signal, evolves with temperature for some organic crystals. , These kinds of PO patterns and their temperature dependence cannot be captured by any superposition of irrep-specific matrices, and a generalization to a fourth-rank formalism is necessary. We argue this is the result of specific phonon–phonon interactions entering the Raman scattering process, an effect which is highly temperature and material-dependent.…”
Section: Introductionmentioning
confidence: 99%
“…However, some of us recently showed that the polarization–orientation (PO) Raman response, i.e., the polarization dependence of the Raman signal, evolves with temperature for some organic crystals. , These kinds of PO patterns and their temperature dependence cannot be captured by any superposition of irrep-specific matrices, and a generalization to a fourth-rank formalism is necessary. We argue this is the result of specific phonon–phonon interactions entering the Raman scattering process, an effect which is highly temperature and material-dependent.…”
Section: Introductionmentioning
confidence: 99%
“…Anharmonic low-frequency phonons are common in molecular materials [27] and can couple to singlets when these approach the Wannier-Mott limit, in a manner which is in turn determined by the size [10] and packing [56] of the molecular building blocks. Our work lays foundations for a deep understanding and controlled enhancement of exciton transport in molecular crystals, for example by suppressing anharmonicity through chemical modifications [57].…”
mentioning
confidence: 97%
“…Below the phase transition temperature, we see red-shifting and broadening of the spectra as temperature increases. These observations are common in temperature-dependent Raman measurements. , Their physical origin is mainly thermal expansion which causes a weakening of the intermolecular interaction (red-shifting) and an increase in phonon population, which decreases the vibrational lifetime (broadening) …”
mentioning
confidence: 99%